2015
DOI: 10.1021/jm501987h
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Plasmodial Serine Hydroxymethyltransferase (SHMT): Cocrystal Structures of Pyrazolopyrans with Potent Blood- and Liver-Stage Activities

Abstract: Several of the enzymes related to the folate cycle are well-known for their role as clinically validated antimalarial targets. Nevertheless for serine hydroxymethyltransferase (SHMT), one of the key enzymes of this cycle, efficient inhibitors have not been described so far. On the basis of plant SHMT inhibitors from an herbicide optimization program, highly potent inhibitors of Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) SHMT with a pyrazolopyran core structure were identified. Cocrystal structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 35 publications
5
71
0
Order By: Relevance
“…The pyrazolopyran core and its alkyl substituents (methyl and isopropyl) were kept intact. [25] Intermolecularh ydrogen bonding is indicated by red dashed lines. a) The one-carbon-unit transfer reaction catalyzed by SHMT.Dihydrofolate reductase (DHFR), SHMT,and thymidylate synthase(TS) are the three enzymes involved in the folate cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pyrazolopyran core and its alkyl substituents (methyl and isopropyl) were kept intact. [25] Intermolecularh ydrogen bonding is indicated by red dashed lines. a) The one-carbon-unit transfer reaction catalyzed by SHMT.Dihydrofolate reductase (DHFR), SHMT,and thymidylate synthase(TS) are the three enzymes involved in the folate cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The same synthetic pathway [25,26] was followed to preparea ll pyrazolopyran-based ligands ((AE)-2-22)r eported in this manuscript (Scheme 1; for the full structures of all ligands, see Ta bles 1a nd 2b elow). Brominated 23 was either converted into the pinacol boronate ester 24 prior to aS uzuki crosscoupling [43] (for (AE)-2-20)o rd irectly subjected to aB uchwald-Hartwig cross-coupling [44] (for (AE)-21 and (AE)-22)l eading to intermediates 25 a-u.As ubsequent Knoevenagel condensation [45] gave access to the dinitrile precursors 26 a-u needed for the one-pot synthesis of the pyrazolopyranc ore involving a Michael addition of 3-methyl-1H-pyrazol-5(4H)-one, followed by an intramolecular cyclization to provide (AE)-2-22 (for details, see the Supporting Information, Section S1).…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Amino acid analogues, such as d ‐serine, d ‐threonine, and thiosemicarbazide, were also investigated, but no significant inhibition was observed either . We recently demonstrated that pyrazolopyran‐based inhibitors, such as carboxylate (±)‐ 18 (Figure ), could inhibit Pf SHMT in the lower nanomolar IC 50 range and were highly effective (half‐maximal effective concentration (EC 50 )) in cell‐based assays against the Pf NF54 strain . Several co‐crystal structures with Pv SHMT showed that these highly preorganized ligands nicely occupy the H 4 F binding pocket of the enzyme.…”
Section: Introductionmentioning
confidence: 99%